Identifikasi Karakteristik Mikroskopik dan Makroskopik pada Jamur Rhizopus sp., Aspergillus sp., dan Penicillium sp., pada Beberapa Sampel Makanan - Liss Dyah Dewi Arini; Fredericus Pramonodjati; Margaretha Alesandria Natasya Weka (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Fungi are microorganisms often found in food and can act as spoilage agents or have certain benefits. Rhizopus sp., Aspergillus sp., and Penicillium sp. are types of fungi commonly found in various foods with different characteristics. This study aims to determine the characteristics of the three fungi, explain the isolation method from food samples, identify morphological and microscopic differences, and analyze factors that influence the success of isolation and identification. The method used was fungal isolation in culture media from food samples, followed by macroscopic and microscopic observations. Data were analyzed descriptively in the form of tables and graphs. The results showed that Aspergillus sp. had the largest number of colonies (12 colonies) with an average diameter of 2.0 mm, Penicillium sp. had the largest diameter (4.5 mm) with 10 colonies, while Rhizopus sp. had 5 colonies with a diameter of 3.0 mm and the fastest growth. Macroscopically, there were differences in color, texture, and shape of the colonies, while microscopically, differences were seen in the type of hyphae, reproductive structure, and characteristics of each fungus. These differences are influenced by environmental factors such as temperature, humidity, substrate type, and the isolation technique used. In conclusion, the three fungi have distinct characteristics and can be identified through morphological and microscopic observations. Maintaining sterility and using a variety of media and environmental conditions is recommended to improve the accuracy of research result.